The Integration Between the Structural System and the Envelope System in Earthquake Resistance Design - Azeez, Ali; AL-Khafaji, Ali (Anbar Journal of Engineering Sciences, 2023)
Earthquakes are one of the most serious natural disasters affecting the stability and the durability of buildings, threatening the life of its occupants. These buildings should be withstanding earthquakes by both architectural and structural engineers. The Integration between structural and envelope system is negatively affected due to; the lack of architectural knowledge in earthquake resistance, and the absence of cooperation between architectural and structural engineers in earthquake resistant design. In this research the lack in the nature of the integrative relationship between the structural and envelope system of earthquake-resistant buildings design is presented. Also, he relationship between these systems, their patterns, and levels in the building to resist earthquakes are highlighted. Where the concept of integration, patterns and levels are verified, using inductive methodology (descriptive, and analytical) through election, analyzing of two different case studies. major result show that the performance pattern is the most common type of three other integration patterns. Also the envelope ,structural system response achieves an equal degree of response as both of them are integrated with each other without revoking one the role of other or affecting the optimal seismic resistance of buildings, and conclusion are presented further.